2016
DOI: 10.1002/14651858.cd009837.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Community-based population-level interventions for promoting child oral health

Abstract: Community-based population-level interventions for promoting child oral health,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 145 publications
3
52
1
2
Order By: Relevance
“…"Upstream" interventions such as reducing price barriers are more likely to have positive effects on alleviating inequalities compared to "downstream" interventions to focus on individual-level factors such as information provided through education. Based on the review of the effects of public health policies on health inequalities, Thomson et al [42] concluded that two types of oral health interventions had positive effects on inequalities: water fluoridation [43] and a national tooth brushing education campaign [44]. Another study pointed out that dental insurance is an important driver for dental service use, as tackling financial barriers mostly reduces unmet dental needs [17,45].…”
Section: Discussionmentioning
confidence: 99%
“…"Upstream" interventions such as reducing price barriers are more likely to have positive effects on alleviating inequalities compared to "downstream" interventions to focus on individual-level factors such as information provided through education. Based on the review of the effects of public health policies on health inequalities, Thomson et al [42] concluded that two types of oral health interventions had positive effects on inequalities: water fluoridation [43] and a national tooth brushing education campaign [44]. Another study pointed out that dental insurance is an important driver for dental service use, as tackling financial barriers mostly reduces unmet dental needs [17,45].…”
Section: Discussionmentioning
confidence: 99%
“…Community water fluoridation and the use of fluoride products (toothpastes, mouthwashes, varnishes and fluoride gel) associated with oral hygiene care has been proven to decrease caries incidence in children and adolescents ,,,,. Indeed, the use of fluoride is part of most preventive programmes,,,,, such as the Baby Clinic programme. In order to avoid bias regarding water fluoride exposition, we included only patients and controls who lived in the Londrina metropolitan region, and had access to fluoride water in childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, attention has been paid to the limited knowledge of the effects of the various interventions carried out in the PDS . A recent Cochrane review found little evidence that for example, oral health education alone could make a difference in the level of caries in the young, although some studies reported improvements in gingival health, oral hygiene behaviours and oral cleanliness, which are clearly important effects. The review concluded that more rigorous measurement and reporting of study results would be needed in order to improve the quality of the available evidence.…”
Section: Discussionmentioning
confidence: 99%